(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
The aim of the study was to investigate the influence of certain microelements (zinc, selenium) on the clinical course of chronic viral hepatitis B (CVHB) in women of reproductive age living in the city of Urgench.